Feedback Modulates Audio-Visual Spatial Recalibration - Kramer, Alexander; Röder, Brigitte; Bruns, Patrick (Frontiers in Integrative Neuroscience, 2020)
In an ever-changing environment, crossmodal recalibration is crucial to maintain precise and coherent spatial estimates across different sensory modalities. Accordingly, it has been found that perceived auditory space is recalibrated toward vision after consistent exposure to spatially misaligned audio-visual stimuli (VS). While this so-called ventriloquism aftereffect (VAE) yields internal consistency between vision and audition, it does not necessarily lead to consistency between the perceptual representation of space and the actual environment. For this purpose, feedback about the true state of the external world might be necessary. Here, we tested whether the size of the VAE is modulated by external feedback and reward. During adaptation audio-VS with a fixed spatial discrepancy were presented. Participants had to localize the sound and received feedback about the magnitude of their localization error. In half of the sessions the feedback was based on the position of the VS and in the other half it was based on the position of the auditory stimulus. An additional monetary reward was given if the localization error fell below a certain threshold that was based on participants’ performance in the pretest. As expected, when error feedback was based on the position of the VS, auditory localization during adaptation trials shifted toward the position of the VS. Conversely, feedback based on the position of the auditory stimuli reduced the visual influence on auditory localization (i.e., the ventriloquism effect) and improved sound localization accuracy. After adaptation with error feedback based on the VS position, a typical auditory VAE (but no visual aftereffect) was observed in subsequent unimodal localization tests. By contrast, when feedback was based on the position of the auditory stimuli during adaptation, no auditory VAE was observed in subsequent unimodal auditory trials. Importantly, in this situation no visual aftereffect was found either. As feedback did not change the physical attributes of the audio-visual stimulation during adaptation, the present findings suggest that crossmodal recalibration is subject to top–down influences. Such top–down influences might help prevent miscalibration of audition toward conflicting visual stimulation in situations in which external feedback indicates that visual information is inaccurate.